Implementasi Model Pembelajaran Cooperative Learning Tipe TPS: Think-Pair-Share dalam Pembejaran Pendidikan Agama Islam: Kajian Literatur - Muzekki; Husnilawati; Imam Syafe’i; Eti Hadiati; Ratu Vina Rahmatika (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Think Pair Share (TPS) cooperative learning model is a learning strategy that aims to improve interaction and collaboration between students. This model consists of three main stages, namely Think (thinking independently), Pair (discussing with a partner), and Share (sharing discussion results with other groups or classes). This study is a literature study that analyzes the application of the TPS model in Islamic Religious Education (PAI) learning and its advantages and disadvantages. The results of the study indicate that the TPS model can increase student participation, develop critical thinking skills, strengthen cooperation in small groups, and increase student self-confidence. However, this model also faces challenges such as the need for good time management, effective coordination, and the difficulty of implementing it in classes with students who are less active or have limited resources. With proper implementation, the TPS model can be an effective method in improving student understanding of concepts and involvement in the learning process.